The Pogogutat Tradition of the Mongondow Tribe in North Sulawesi on Maslahah Mursalah Perspective - Aswar R. Mamonto; Nova Effenty Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2019)
This study aims to discuss the Mongondow tribal pogogutat tradition in North Sulawesi with a maslahah mursalah approach. This research is field research and data collected through observation, interviews and documents. The collected data were analyzed by qualitative descriptive through fiqh approach, namely the problem masseah. The results showed: First, there was a shift in the practice of pogogutat, starting from the business of making tent services, catering services, increasing people's income, without the terms and conditions of the goods. Pogogutat value shift due to lack of social life, tribal and cultural assimilation, village government regulations, lack of community awareness in understanding local culture, lack of cultural communication, lack of cultural learning and pogogutat tradition, environmental changes, and the influence of modern culture; Second, although the Pogogutat tradition has negative values, the Pogogutat tradition tends to have positive values ​​as a primary need (darûriyât).